2006
DOI: 10.1088/0954-3899/34/2/011
|View full text |Cite
|
Sign up to set email alerts
|

Probing nuclear skins and halos with elastic electron scattering

Abstract: I investigate the elastic electron scattering off nuclei far from the stability line. The effects of the neutron and proton skins and halos on the differential cross sections are explored. Examples are given for the charge distribution in Sn isotopes and its relation to the neutron skin. The neutron halo in 11 Li and the proton halo in 8 B are also investigated. Particular interest is paid to the inverse scattering problem and its dependence on the experimental precision. These studies are of particular intere… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
51
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 43 publications
5
51
0
1
Order By: Relevance
“…Rather, it is due only to the coupling of the 4 extra neutrons to the 7 Li core. A similar conclusion has been reached by Bertulani [7].…”
supporting
confidence: 87%
See 1 more Smart Citation
“…Rather, it is due only to the coupling of the 4 extra neutrons to the 7 Li core. A similar conclusion has been reached by Bertulani [7].…”
supporting
confidence: 87%
“…However, they did not make any conclusion as to the role of the neutron halo character of 6 He. That role, of the halo in elastic electron scattering, was sought more recently by Bertulani [7]. He also used the Helm model and found that the contribution from the neutron halo itself was insignificant.…”
mentioning
confidence: 94%
“…But as already noticed [20], the rms radii (second moments of the densities) provide a very limited description of the nucleon density distributions. A more effective tool to analyze skins [20,34] is the Helm model [32,33]. This is a model that allows one to extract from the form factor in a simple way the two main characteristics of the density: a diffraction radius and a surface thickness.…”
Section: B Form Factors and Diffraction Parametersmentioning
confidence: 99%
“…The latter was shown to have a smooth gradual dependence on the neutron excess and to be almost unaffected by shell effects. The Helm model was used very recently also by Bertulani [34] to investigate electron scattering from light unstable nuclei.…”
Section: Introductionmentioning
confidence: 99%
“…Collective vibrations of nuclei are also a good tool to investigate the symmetry energy. Some features of neutron rich nuclei are also though to be very sensitive to the the symmetry energy, such as their neutron skin ∆r = r p − r n , where r p(n) is the proton (neutron) matter distribution [289,290]. Collective vibrations in neutron-rich nuclei at low energies are usually so-called Pigmy Resonances or Ikeda resonances [188,191,[291][292][293].…”
Section: A Collective Resonances Neutron Skins and Neutron Starsmentioning
confidence: 99%